California Drug and Alcohol Treatment Assessment (CALDATA), 1991-1993 ([Verlag nicht ermittelbar], 2004)
The California Drug and Alcohol Treatment Assessment (CALDATA) was designed to study the costs, benefits, and effectiveness of the state's alcohol and drug treatment infrastructure (recovery services) and specifically to assess (1) the effects of treatment on participant behavior, (2) the costs of treatment, and (3) the economic value of treatment to society. Data were collected on participants (clients) across four types of treatment programs, or modalities: residential, residential "social model," nonmethadone outpatient, and outpatient methadone (detoxification and maintenance). Data were collected in two phases. In Phase 1, treatment records were abstracted for clients who received treatment or were discharged between October 1, 1991, and September 30, 1992. In Phase 2, these clients were located and recruited for a follow-up interview. The CALDATA design and procedures included elements from several national treatment outcome studies including the Drug Services Research Survey (ICPSR 3393), Services Research Outcomes Study (ICPSR 2691), National Treatment Improvement Evaluation Study (ICPSR 2884), and Drug Abuse Treatment Outcome Study (ICPSR 2258). The record abstract was designed to collect identifying and locating information for interview reference during the personal interviewing phase. The abstract also collected demographic, drug, or alcohol use, and treatment and service information. The follow-up questionnaire covered time periods before, during, and after treatment and focused on topics such as ethnic and educational background, drug and alcohol use, mental and physical health, HIV and AIDS status, drug testing, illegal activities and criminal status, living arrangements and family issues, employment and income, and treatment for drug, alcohol, and mental health problems. Drugs included alcohol, barbiturates, benzodiazepines, cocaine powder, crack, downers, hallucinogens, heroin, illegal methadone, inhalants, LSD, marijuana/hashish/THC, methamphetamines and other stimulants, narcotics, over-the-counter drugs, PCP, ritalin or preludin, and sedatives/hypnotics. CALDATA was originally known as the California Outcomes Study (COS).